Structural Improvement of the ω-Type High-Speed Rail Clip Based on a Study of Its Failure Mechanism - Xiaogang Gao; Anbin Wang; Yu He; Xiaohan Gu (Shock and Vibration)
In the circumstances of high-speed railways, the wheel-rail vibration is significantly aggravated by polygonal wheel wear and rail corrugation, which subsequently leads to the wheel-rail interaction at higher frequencies and potential failure of the rail fastening. In this paper, a ω-type clip of the fastening in the CRH high-speed rail was used to investigate the failure mechanism. First, a dynamic wheel-rail coupling model and a finite element analysis of the rail clip were developed, from which the rail vibration frequency and modal frequencies of the clip with different installation torques were obtained. The experimental tests and modal simulation results were mutually verified. In addition, the real-time vibration measurement and the wheel-rail wear monitoring were carried out at a CRH high-speed railway site. It was found that the resonant frequencies of the ω-type clip in the installation condition coincided with the excitation frequencies of the wheel-rail interaction induced by wheel-rail wear. The high-frequency dynamic failure mechanism of a typical ω-type clip, W300-1, is put forward for the first time. Moreover, a high-frequency rail clip fatigue test system was designed and developed specifically for this study. The loading excitation frequency of the clip test used was set as 590 Hz, and the loading amplitude was 0.05 mm. After 125-minute operation of the test system, the clip was broken at the expected location predicted by the FEA model. The high-frequency fatigue test result further verified that the failure mechanism of the ω-type clip was due to the resonance of the clip with its excitation force from the wheel-rail interaction. Finally, the clip was then structurally improved taking into account the stiffness and mass, which led to its resonant frequencies shifting away from the high-frequency excitation range, hence avoiding resonance failure of the subject clip.